1985
DOI: 10.1302/0301-620x.67b3.3997939
|View full text |Cite
|
Sign up to set email alerts
|

Spinal brucellosis

Abstract: Twenty-one patients with spinal brucellosis were reviewed. The disease is difficult to diagnose, and is often confused with spinal tuberculosis. Our study showed that it was best diagnosed by serology 2nd bacterial culture; radiography and scanning were less helpful in the early stages. After only six weeks' antibiotic treatment, there was a 55% clinical and serological reactivation rate: better results were achieved after at least three months of treatment. The adequacy of treatment was best monitored with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
80
0
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 0 publications
11
80
0
7
Order By: Relevance
“…3,6,7 Spondylitis is one of the most frequently a ected sites in adults, accounting for between 20% to 60% of osteoarticular complications, the lumbar segment being the most commonly a ected level, varying in frequency from 44% to 76% according to di erent studies. 6,8 ± 10 Although brucella spondylitis is considered a mild form of infectious spondylitis in some reports, 11,12 in others, and in our case report, it caused highly destructive lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,6,7 Spondylitis is one of the most frequently a ected sites in adults, accounting for between 20% to 60% of osteoarticular complications, the lumbar segment being the most commonly a ected level, varying in frequency from 44% to 76% according to di erent studies. 6,8 ± 10 Although brucella spondylitis is considered a mild form of infectious spondylitis in some reports, 11,12 in others, and in our case report, it caused highly destructive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…5 ± 7 The best results have been obtained with doxycycline and streptomycin treatment so far. 3 Lifeso et al 6 suggested that the duration of therapy was more important than the antibiotic agent itself. Surgical drainage is usually recommended along with prolonged antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While arthritis, bursitis, tenosynovitis, and sacroiliitis are more frequently observed in younger patients, the frequency of spondylodiscitis increases with aging, and its diagnosis may be difficult. [1][2][3][4] In this paper, we report a patient first misdiagnosed in another clinic as having a tumor or tuberculosis. The patient presented with paraplegia due to a compression fracture and a paravertebral soft tissue mass in the thoracic spine, which was later found out in our clinic to be due to brucellar spondylitis.…”
Section: Introductionmentioning
confidence: 99%
“…3 The earliest features are mild osteoporosis and epiphysitis localised in the anterio-superior angle, followed by narrowing of the joint space and involvement of the contiguous vertebral. 4,5 As the interosseous infection progresses with increasing vertebral body destruction, a delineating rim of sclerosis develops with subsequent anterior and lateral osteophytosis. 4 Posterior elements of the spine are rarely involved.…”
Section: Introductionmentioning
confidence: 99%